ANALISIS BIAYA PERAWATAN DAN PERBAIKAN JEMBATAN BAJA JEMBATAN SUNGAI KEMBUNG LUAR - Syamsuriyadi, Syamsuriyadi; Gunawan, Gunawan (Jurnal TeKLA, 2024)
In everyday life, the bridge is a means of accommodation that supports the smooth flow of traffic around the world, including Indonesia. A bridge is a structure that is built across rivers or other traffic barriers, so if a bridge is damaged, this is felt to disturb the comfort of traffic. One of the problems of bridge damage that occurred was damage that occurred beyond estimates that required inspection to get the right action. The purpose of this study is to analyze the estimated cost of maintaining and repairing steel bridges.            The research method used in this research is descriptive quantitative. One of the problems of bridge damage that occurred was damage that occurred beyond estimates that required inspection to get the right action. After conducting a direct survey, it was found that the damage had occurred and this research refers to the 2018 revision of the 2nd revision of the 2018 Bina Marga, so maintenance and repairs have been arranged in division 8 and division 10. The estimated cost of maintaining / repairing the Sungai Kembung Luar bridge is IDR 340,640,000. 00 and as for the estimated cost of work that occurs repeatedly on the Sungai Kembung Luar bridge for the next 30 years, it amounts to IDR 1,492,383,104.41.